Review papers Some molecular aspects of the fibroproliferative process in keloids - Paweł Antończak; Magdalena Jurzak; Katarzyna Adamczyk; Agnieszka Garncarczyk (Termedia Publishing House, 2015)
Reparation of damaged tissues is an essential biological process that ensures maintenance of homeostasis. Basically it includes phases of inflammation, proliferation and remodeling. The result of healing of damaged tissues is scar formation. Abnormalities in the course of wound healing may lead to keloid formation. The pathophysiology of keloids is characterized by improper migration, proliferation and apoptosis of cells as well as imbalanced synthesis and secretion of proteins, cytokines, proteolytic enzymes and their inhibitors. To date, applied therapeutic methods do not lead to satisfactory cosmetic results of the treatment. Current research focuses on developing methods for direct inhibition of the fibroproliferative process, mainly through modulation of cytokine expression and in consequence suppression of fibroblast proliferation and balancing of synthesis and degradation of extracellular matrix components.